The Reality of the Struggle of the Indonesian Nation in the National Revolution Era in the Novel Burung-Burung Manyar by Y.B. Mangunwijaya - Emawati, Emawati; Wicaksono, Andri (IJLECR (International Journal of Language Education and Cultural Review), 2024)
The historical reality in the Indonesian novel with the perspective of New Historicism is a theoretical and practical study that focuses on historical and literary issues. The Indonesian novel that became the focus of the study was the work of Y.B. Mangunwijaya, namely Burung-Burung Manyar that represent historical events of the struggle of the Indonesian (Year 1945-1949) in a different color from historical texts in general. Therefore, this study aims to describe in depth the objective reality of the nation’s struggle during the national revolution in the novel Burung-Burung Manyar by Y.B. Mangunwijaya. The research method used is qualitative interpretive with parallel reading between literary texts at events which represent the historical representation of the nation’s struggle. Data collection techniques with documentation with the main instrument is the researcher assisted by tabulation of objective reality data in the novel Burung-Burung Manyar by Y.B. Mangunwijaya. Data analysis techniques begin with data reduction, data presentation, and drawing conclusions. The results showed that the objective reality studied was historical facts originating from artifacts or in the form of objects, relics and places, then social life, mental conditions, and ecology. Furthermore, the events, places and characters contained in the novel are imaginative, but in them there are hidden facts. When linked with fact and fiction, reality and fiction in a broad sense, history turns out to be in conflict with literature. The objective reality in the course of history is realist statement.